Protein Phosphorylation Changes During Systemic Acquired Resistance in Arabidopsis thaliana - Zhou, Qingfeng; Meng, Qi; Tan, Xiaomin; Ding, Wei; Ma, Kang; Xu, Ziqin; Huang, Xuan; Gao, Hang (Frontiers in Plant Science, 2021)
Systemic acquired resistance (SAR) in plants is a defense response that provides resistance against a wide range of pathogens at the whole-plant level following primary infection. Although the molecular mechanisms of SAR has been extensively studied in recent years, the role of phosphorylation that occurs in systemic leaves of SAR induced plants is poorly understood. We used a data-independent acquisition (DIA) phosphoproteomics platform based on high-resolution mass spectrometry in an Arabidopsis thaliana model to identify phosphoproteins related to SAR establishment. 8011 phosphorylation sites from 3234 proteins were identified in systemic leaves of Pseudomonas syringae pv. maculicola ES4326 (Psm ES4326) and mock locally inoculated plants. 859 significantly changed phosphoproteins from 1406 significantly changed phosphopeptides were detected in systemic leaves of Psm ES4326 locally inoculated plants, including numerous transcription factors and kinases. A variety of defense response-related proteins were found to be differentially phosphorylated in systemic leaves of Psm ES4326 locally inoculated leaves, suggesting these proteins may be functionally involved in SAR through phosphorylation or dephosphorylation. Significantly changed phosphoproteins were enriched mainly in categories related to plant-pathogen interaction, MAPK signaling pathway, purine metabolism, photosynthesis-antenna proteins and flavonoid biosynthesis. 28 proteins were regulated at both protein and phosphorylation levels during SAR. qRT-PCR analysis revealed that changes of phosphorylation levels of proteins during SAR did not result from changes of transcript abundance. This study provides comprehensive details of key phosphoproteins associated with SAR, which will facilitate further research on molecular mechanisms of SAR.